The Art of Nurse Mentoring: A Framework of Support - Diane S. Kramer; Victoria Y. McCue; Eve Butler; Andrea S. Prentiss; Maria M. Ojeda; Kayce K. Tugg; Vivian Fuentes; Sally Bonet (Library & Knowledge Services and Nursing & Health Sciences Research Departments, 2021)
Introduction: Nursing mentoring relationships are vital to the advancement of personal and professional growth in nursing. Mentoring has been identified as an effective method to decrease turnover resulting in retention of experienced nurses. Despite the benefits of a mentoring relationship, barriers exist in creating and cultivating a formal mentoring program in the hospital setting. Methods: A qualitative descriptive study approach that explored nurses' perceptions of a mentoring culture within a hospital environment. Open-ended, conversational-style interviewing techniques with a semi-structured interview guide were utilized to gain a full description of nurses' perceptions of a mentoring culture within a hospital environment. Results: A structural model of mentoring as perceived by hospital nurses was developed from the data. Five overarching themes with corresponding subthemes emerged from nurses' perceptions. (1) Mentoring culture: various mentoring models, informal vs formal, leader focused, and evolving. (2) Benefits: connections, development, retention, stability, patient safety, and making a difference. (3) Barriers: time, patients/patience, competition, knowledge deficit regarding mentor verses preceptor roles, lack of incentives, receptiveness, and voluntold. (4) Experience with mentoring: going above and beyond, lifetime relationships, personal/professional growth, feeling cared for. (5) Paradigm shift: match generational and cultural differences, resources, face-to-face, and voluntary. Discussion: The study results have identified mentoring as an integral aspect of personal and professional growth within the hospital environment. The rewards of mentoring or being mentored can be translated into increased nursing retention and improved nursing job satisfaction.